Encountering the parables in contexts old and new - European Association for Biblical Studies 2018 Helsinki; Goud, Thomas E.; Cousland, J. R. C.; Harrison, John (London New York Oxford New Delhi Sydney t&t Clark, 2023)
"This volume examines the material elements and mundane aspects of daily life in the first century that underlie Jesus' Synoptic parables"--
Literaturangaben
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Jesus Christ -- Parables; Konferenzschrift -- 2018 -- Helsinki; Aufsatzsammlung